Inorganic Material of Magnesium Nitrate Mg(NO3)2 Film as Q-Switcher in the C-Band Region - Zalkepal, Noor Ummi Hazirah Hani; Mohammed Bakr Alsaady, Muwafaq; Mudhafar, Mustafa; Nik Mahmud, Nik Noor Haryatul Eleena; Muhammad, Nur Ainnaa Mardhiah; Muhammad Zamri, Ain Zamira; Awang, Noor Azura (Pertanika, 2024)
A novel inorganic material of Magnesium Nitrate (Mg(NO3)2) thin film is successfully investigated in the C-band region. The Q-switcher is Mg(NO3)2 thin film. The solvent casting method has been applied to prepare Mg(NO3)2 thin film before being positioned within the fiber ferrule duo to act as a Q-switcher. Thereby, the modulation depth and the saturation intensity of the Mg(NO3)2 thin film exhibit at 32.40% and 0.07 MW/cm2 , respectively. It is possible to produce a steady Q-switched pulse fiber laser with a maximum pump power of 403.00 mW, a repetition rate of 72.56 kHz, and a pulse width of 3.00 µs. In addition, the tunable Q-switched pulse fiber laser is also examined using a figure-of-eight cavity design incorporating a tunable bandpass filter (TBF). Consequently, the operating wavelength is changed in the range of 1528 nm to 1552 nm, even while the pump power remains the same at 403.00 mW. During this time, the pulse width and repetition rate shifted from 2.10 µs to 4.10 µs and altered from 67.90 kHz to 35.80 kHz, respectively. Consequently, the Mg(NO3)2 thin film has the opportunity to be an effective saturable absorber for generating pulsed fiber lasers and can be applied in optical communications applications.